The Influence Of Workload And Working Environment On Employee Performance At PT. XYZ In Tangerang - Aprilia, Aprilia; Effendy, Aidil Amin (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2025)
The purpose of this study was to determine the effect of workload and work environment on employee performance at PT. XYZ both partially and simultaneously. The method used is the associative quantitative method. The sampling technique used is saturated sampling using a sample of 68 respondents. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-test and f-test. The results of this study are that the workload does notsignificantly influence employee performance with the regression equation Y = 58.934 - 0.408X1, the correlation value of -0.398 means that the relationship between the two variables is negative with a low level of relationship with a coefficient of 15.9%. Hypothesis testing obtained t count 3.14) then H0 is rejected and H3 is accepted, meaning that there is a significant simultaneous influence between workload and work environment on employee performance at PT. XYZ in Tangerang.